The Use of Artificial Intelligence among Students in Higher Education - Jereb Eva; Urh Marko (Organizacija)
Artificial intelligence (AI) impacts our everyday lives, from business to social areas, and, in recent years, more and more education. This paper aims to discuss using artificial intelligence tools for educational purposes from the student’s perspective.